Diagnosis and management of community-acquired urinary tract infection in infants and children: Clinical guidelines endorsed by the Saudi Pediatric Infectious Diseases Society (SPIDS) - May Albarrak (International Journal of Pediatrics and Adolescent Medicine, 2021)
Urinary tract infection (UTI) is the most common bacterial disease in childhood worldwide and may have significant adverse consequences, particularly for young children. In this guideline, we provide the most up-to-date information for the diagnosis and management of community-acquired UTI in infants and children aged over 90 days up to 14 years. The current recommendations given by the American Academy of Pediatrics Practice guidelines, Canadian Pediatric Society guideline, and other international guidelines are considered as well as regional variations in susceptibility patterns and resources. This guideline covers the diagnosis, therapeutic options, and prophylaxis for the management of community-acquired UTI in children guided by our local antimicrobial resistance pattern of the most frequent urinary pathogens. Neonates, infants younger than three months, immunocompromised patients, children recurrent UTIs, or renal abnormalities should be managed individually because these patients may require more extensive investigation and more aggressive therapy and follow up, so it is considered out of the scope of these guidelines. Establishment of children-specific guidelines for the diagnosis and management of community-acquired UTI can reduce morbidity and mortality. We present a clinical statement from the Saudi Pediatric Infectious Diseases Society (SPIDS), which concerns the diagnosis and management of community-acquired UTI in children.